2018
DOI: 10.1002/csr.1499
|View full text |Cite
|
Sign up to set email alerts
|

Environmental policy and sustainable development: An empirical study on carbon reduction among Chinese enterprises

Abstract: This study mainly examined the influences of enterprises' carbon reduction behaviors on their sustainable development, and investigated the effects on sustainable development of carbon emission reduction by state-owned enterprises (SOEs) from high-carbon-emission industries in China. Data were coded through a content analysis procedure, followed by regression analysis.Analysis of variance results revealed that SOEs and high-carbon-emission industries emphasize realizing carbon reduction more than do privately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Arora et al [13] used panel data regression to study the associations among the asset turnover, financial leverage, net profit margin, and SGR of the Indian manufacturing sector's firms listed on the National Stock Exchange of India Ltd., between 1998 and 2014. Yu and Tsai [38] used the regression model to explore the effect of environmental policy on sustainable development in Chinese enterprises. Mamilla [12] used the linear regression method to study the relationship between asset efficiency, financial leverage, firm size liquidity, and SGR for the oil refineries industry in India.…”
Section: Sustainable Growth Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Arora et al [13] used panel data regression to study the associations among the asset turnover, financial leverage, net profit margin, and SGR of the Indian manufacturing sector's firms listed on the National Stock Exchange of India Ltd., between 1998 and 2014. Yu and Tsai [38] used the regression model to explore the effect of environmental policy on sustainable development in Chinese enterprises. Mamilla [12] used the linear regression method to study the relationship between asset efficiency, financial leverage, firm size liquidity, and SGR for the oil refineries industry in India.…”
Section: Sustainable Growth Ratementioning
confidence: 99%
“…Like the ESG scores, Morningstar's rating uses a 0-100 scale, where lower scores are superior. ESG risk is divided by five risk levels: negligible (0-10), low (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), medium (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), high (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), and severe (40-100) [19].…”
Section: Variablesmentioning
confidence: 99%
“…China has already put forward a policy of building an ecological civilization, and low-carbon development is also an inevitable choice, which will play an important role in alleviating environmental pressure and reversing the situation of continued deterioration of the ecological environment. Carbon reduction positively and significantly influences corporate sustainable development [12]. Carbon information disclosure is an important issue in the development of low-carbon, which has widely concerned stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…Using large Italian firms, Cucchiella et al [39] found that cutting down carbon emissions has beneficial effects on the financial performance of a firm. This was supported by Yu and Tsai [47] who alluded that efforts by a firm to cut down its carbon emissions improve the longevity and sustainability of the firm. Lewandowski [48] also found a significant positive relationship between carbon emission reduction and financial performance.…”
Section: Carbon Emission Reduction and Financial Performancementioning
confidence: 96%
“…The results indicated that cutting down carbon emissions offers a business sustainable benefits. Yu and Tsai (2018) [ 47 ] concur and allude that efforts by a firm to cut down its carbon emissions improves its longevity and sustainability. This is because it is now crucial than ever to excel in environmental performance.…”
Section: Introductionmentioning
confidence: 99%